2012
DOI: 10.4269/ajtmh.2012.11-0532
|View full text |Cite
|
Sign up to set email alerts
|

Enzootic Angiostrongyliasis in Guangzhou, China, 2008–2010

Abstract: Abstract. This study was conducted to gain an understanding of the Angiostrongylus cantonensis infection status of rodent definitive host, snail intermediate host, and local residents in Guangzhou, China. A total of 430 rats were captured and 23 rats, from two species, were infected, with an average infection rate of 5.35%. A total of 795 Achatina fulica snails and 734 Pomacea canaliculata snails were collected. The average infection rates of these two species were 13.96% (111 of 795) and 1.50% (11 of 734), re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
6
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 10 publications
(20 reference statements)
0
6
1
Order By: Relevance
“…In comparison with some other cities/provinces in China, e.g., Shenzhen [ 26 ] and Xiamen [ 27 ] and Hainan [ 28 ], the infection rates of P. canaliculata were lower than those from our findings, but they were higher in Dali [ 29 ] and Guangzhou [ 30 ]. However, our reported rate of infected rats was lower than those reported in Rio de Janeiro in Brazil [ 31 ], Canary Islands [ 32 ] and Nueva Ecija in the Philippines [ 33 ]; while it was higher than those found in Guangzhou [ 34 ] and Zhongshan [ 35 ] in China.…”
Section: Discussioncontrasting
confidence: 78%
“…In comparison with some other cities/provinces in China, e.g., Shenzhen [ 26 ] and Xiamen [ 27 ] and Hainan [ 28 ], the infection rates of P. canaliculata were lower than those from our findings, but they were higher in Dali [ 29 ] and Guangzhou [ 30 ]. However, our reported rate of infected rats was lower than those reported in Rio de Janeiro in Brazil [ 31 ], Canary Islands [ 32 ] and Nueva Ecija in the Philippines [ 33 ]; while it was higher than those found in Guangzhou [ 34 ] and Zhongshan [ 35 ] in China.…”
Section: Discussioncontrasting
confidence: 78%
“…The diversity of gastropods now known to carry Angiostrongylus cantonensis encompasses a broad phylogenetic range of both terrestrial and freshwater species ( Figure 3 ; Appendix S1 ). A single fully marine species ( Discotectonica acutissima : Architectonicidae) has also been reported as testing positive for A. cantonensis [57] but this is a sublittoral (50–200 m depth) species [58] and the finding may be incorrect. Previous studies had identified species in 33 families as natural hosts of A. cantonensis , with the present study adding three more: Achatinellidae, Assimineidae and Oxychilidae.…”
Section: Discussionmentioning
confidence: 99%
“…Prevention and control of this foodborne zoonotic disease is a matter of considerable importance, and for this preventing infection is the most essential step [17], [18]. However, A. cantonensis infection can take place not only by ingestion of intermediate hosts but also by ingestion of vegetables and drinking water and through hand-to-mouth contact after touching a contaminated object [3], [19].…”
Section: Discussionmentioning
confidence: 99%